Social and psychological support of students from rural areas in the conditions of a higher education institution - Kravchenko, Oksana (Психологічний журнал, 2023)
The article establishes that an important direction of gender policy is to ensure equal rights and opportunities for women from rural areas, including the realization of their human rights. Obviously, it’s time for the development of appropriate organizational, educational, and socio-educational conditions for the social formation of student youth in a higher education institution, including girls from rural areas, which is a prerequisite for their successful socialization, observance of the rights to equal access to education, involvement in social activities, and formation as full participants in human relations.